Damage of Siloxanes on Ni‐YSZ Anode Supported SOFC Operated on Hydrogen and Bio‐Syngas1. Issue 5 (3rd September 2015) - Madi, H.; Diethelm, S.; Poitel, S.; Ludwig, C.; Van herle, J.; Christiansen, Niels; Hagen, Anke; Bele, Petra; Bucheli, Olivier
Abstract This work presents the poisoning effect of organic oxo‐silicon compounds (siloxanes) which are generally found in sewage biogas. Lifetime and durability associated with solid oxide fuel cell (SOFC) technology is strongly related to the amount of contaminants that reach the stack. Several experiments on Ni anode‐supported (AS) single cells are performed in order to clarify the mechanism of degradation and also the possibility of cell performance recovery. Three experiments focus on the degradation and recovery of AS Ni‐YSZ fed with H2, co‐feeding 5 ppm D4‐siloxane (octamethylcyclotetrasiloxane, C8H24O4Si4) as representative compound for the organic silicon species, at 800 °C. A fourth experiment focuses on the durability of the AS Ni‐YSZ cell with variable concentrations of the impurity (0–5 ppm), during steady state polarization (0.25 A cm−2) for 250 h, using simulated biogas‐reformate fuel H2/CO/CO2/H2O: irreversible degradation was observed with the D4‐impurity feed in the anode gas. Post‐test scanning electron microscopy (SEM) results indicate formation of SiO2(s) deposits, which block pores and reduce the TPB length.